A qualitative enquiry on the impact of mental illness stigma on caregiving role and experiences in Singapore - Ong, Wei Jie; Goh, Chong Min Janrius; Tan, Gregory Tee Hng; Shahwan, Shazana; Subramaniam, Mythily (Frontiers in Psychiatry, 2024)
Given that mental illness stigma is a common occurrence amongst people with mental illness and caregiver (CG) can be a potential victim of stigma themselves, there is a need to examine caregivers' perspective on the phenomenon. This study is part of a larger study which aims to qualitatively examine the concept of mental illness stigma amongst different stakeholders in Singapore. Focus group discussions (FGDs) were conducted amongst 21 informal caregivers to explore the experience of stigma encountered by their care recipients and themselves, and how it may implicate their caregiving experience. Both inductive and deductive thematic analyses were employed to analyze the data. Three overarching themes of stigma encounters that may have implication on caregiving experience were identified: 1) Stigma within the family; 2) Structural stigma; and 3) Stigma by association. Experience of stigma within family (e.g., social exclusion and lack of understanding) limits the caregiving supports available to CGs. CGs also took up mediating role between their care recipients and other family who may hold stigmatizing views. Witnessing their care recipients being subjected to structural disadvantages (e.g., employment, school, and mandatory conscription) can induce emotional stresses amongst CG and motivate them to protest and seek redress on their behalf. Furthermore, encounters of stigma themselves (e.g., being judged or blame for their loved one's condition) also lead to guilty and self-blames amongst the CGs. These findings can aid the formulation of interventions in informing CGs on what to expect on their caregiving journey and supporting them in dealing with issues relating to stigma and highlight the importance of anti-stigma efforts in organizational setting such as schools, corporations, and government agencies.